KONSTRUKSI SOSIAL PELECEHAN SEKSUAL VERBAL (CATCALLING) PADA MAHASISWA PELAKU PELECEHAN SEKSUAL VERBAL (CATCALLING) DI UNIVERSITAS SRIWIJAYA - Fadhilah , Nurul (PT. Anagata Sembagi Education, 2024)
This research analyzes the externalization process, objectivation process, and internalization process of catcalling students at Sriwijaya University. This research uses a descriptive qualitative approach method with collection techniques and uses observation, interviews, and documentation. The theory used in this research is the Social Construction Theory of Peter L Berger and Thomass Luckmann. The results showed that someone who does catcalling is due to the influence of others. And it is not uncommon for the perpetrators to realize that catcalling is an action that is not good and only for their own satisfaction, but awareness of this does not make the perpetrators stop catcalling..